Drug biophysical profiling using lipid-based colloidal nanosystems and human serum albumin as biomimetic interfaces - Fernandes, Eduarda Barbosa (2017)
[Excerpt] Why? In the drug discovery process it should be considered that in physiological environment there will be reciprocal interactions between drugs and biological interfaces, such as cell membranes or plasma proteins, and from those interactions different pharmacokinetic profiles can be achieved.[...]